Building an event ontology for historical domain to support semantic document retrieval - Fatihah, Ramli; Shahrul Azman, Mohd Noah (Insight Society, 2016)
In the past years, there has been increasing concern on ontology for its ability to explain data semantics in the usual manner independent of the data source characteristics, providing a schema that allows interchanging data between heterogeneous information systems and users. The ontology development in some areas is not expected due to a large amount of information, particularly in history, leading its semantic impossible. Several works have been designed to improve the technological aspects of ontology, such as the representation of language and inference mechanisms, and less attention has been paid to practical results development of application methods. This paper presents a discussion on the experience and processes during ontology building in history: historical documents retrieval based on the event